Progress and political decision-making: A contribution to the enlightenment of the concept of progress - Vorderstraße, Stefan (Momentum Quarterly, 2014)
The term ‘progress’ is closely related to the concept of modernity. Based on continual scientific and technical innovations the concept of progress implicated the capacity of mastering the future for long time. The debate in the social sciences followed with a time lag and took place on the predictability and controllability of social processes. The links between the idea of progress and political decision-making were and will be apparent in these debates. In this paper the idea of progress shall be regarded in the dimension of time. The focus is being strengthened on the temporal implications of the concept of progress. In the light of contemporary social constellations it is examined how the concept of progress can be theoretically designed. How can our understanding of progress be defined? Finally the re-actualized term of progress is being linked to the issue of political decision-making.
Keywords: progress; time; political decision making; system theory